EFEKTIVITAS MEDIA MANIPULATIF UNTUK MENINGKATKAN KEMAMPUAN MENGENAL NILAI TEMPAT PADA ANAK KESULITAN BELAJAR KELAS IV DI SD NEGERI 09 KOTO LUAR PADANG - Nika Sri Rahayu; Kasiyati Kasiyati (INCARE, International Journal of Educational Resources, 2020)
This research discusses the problems found in SD N 09 Koto Luar Padang namely 10 year old learning difficulties in the ability to recognize the value of the place. The study aims to reveal whether the manipulative media can improve the value of the place in the child's difficulty learning. The methods used are Single subject research (SSR) with A-B-A design. Collect and measure all data in a baseline condition one (A-1) continuously over four times the meeting. Providing intervention using manipulative media (B) is implemented during eight meetings. Provides a second baseline (A-2) for four times the meeting. The technique of collecting data on this research by giving tests. Based on the results of data analysis in conditions that demonstrate increased ability to know the value of place. Overlapping analysis data between conditions, at baseline (A-1) and Intervention (B) is 0% and overlapping baseline condition data (A-2) and 0% intervention. Based on the results of the data analysis shows that manipulative media can improve the ability to know the value of the place in children learning difficulties.